Bundling Justice: Medicaid's Support for Housing. Issue 3 (September 2018) - Crossley, Mary
Should Medicaid pay for supportive housing for homeless persons? After describing current limits on how states can use Medicaid funds to support housing, this article considers whether justice requires treating Medicaid recipients residing in nursing homes and Medicaid recipients needing supportive housing similarly.